Species-specific response to acute hyperthermal stress of Haworthia (Asphodelaceae) plants - N. V. Nuzhyna; M. M. Gaidarzhy; Y. V. Aviekin (Regulatory Mechanisms in Biosystems, 2017)
An increase in environmental temperature is one of the most common stress factors for plant organisms. The study of the plants’ adaptation to stress factors remains extremely important and relevant. This article presents the results of a acute short-term influence of hyperthermia on species of two subgenera of the genus Haworthia Duval. We investigated the different levels of antioxidant protection and damage degree of the members of two subgenera of the genus Haworthia at the biochemical level, measuring the lipid peroxidation, superoxide dismutase and peroxidase activities, total flavonoid content and content of photosynthetic pigments with a spectrophotometer. To determine the drought tolerance of plants, the water supply of tissues, water shortage and loss of water after an hour of wilting were measured. The values for different groups were compared by ANOVA followed by the Tukey multiple comparison test. The studied plants were warmed in a thermostat at temperatures of 40 °C and 50 °C for three hours under the conditions of natural light. The control group of plants was kept at 25 °C. The research has shown that H. attenuata, H. limifolia and H. cymbiformis are characterized with the increase of concentration of malonic dialdehyde at 40 °C and 50 °C, but a significant difference of values wasn’t received,which indicates the relative resistance of these plants to the influence of high temperatures. The sharp increase of temperature causes the highest level of lipid peroxidation in H. parksiana plants, along with which, warming to 50 °C launches a mechanism of activation and synthesis of superoxide dismutase and flavonoids for the plants. The studied species of the subgenus Haworthia have a photosynthetic system relatively resistant to thermal stress in comparison to the subgenus Hexangulares. H. limifolia plants have a slight inhibition of photosynthesis. The adaptation of H. cymbiformis to thermal stress is due to the strategy of accumulation of a pool of active enzymes, superoxide dismutase, peroxidase, flavonoids under normal conditions and the activation of new peroxidase enzymes as a result of stress. H. attenuata is characterized by activation of new enzymes of superoxide dismutase and peroxidase under stress. It was found that H. cymbiformis and H. attenuata are more heat resistant in comparison with the other two species. Acute short-term hyperthermia has a different influence on the antioxidant system of different species of Haworthia. H. limifolia has the highest drought tolerance, H. cymbiformis has the lowest, the other two species from different subgenera have similar drought tolerance indicators. We did not find any dependence of the mechanisms of action of the antioxidant system under hyperthermia on the type of adaptation to arid conditions at the anatomical level in plants of different subgenera of the genus Haworthia.